Comparison of "warm and wet" and "cold and icy" scenarios for early Mars in a 3‐D climate model. Issue 6 (26th June 2015) - Wordsworth, Robin D.; Kerber, Laura; Pierrehumbert, Raymond T.; Forget, Francois; Head, James W.
Abstract We use a 3‐D general circulation model to compare the primitive Martian hydrological cycle in "warm and wet" and "cold and icy" scenarios. In the warm and wet scenario, an anomalously high solar flux or intense greenhouse warming artificially added to the climate model are required to maintain warm conditions and an ice‐free northern ocean. Precipitation shows strong surface variations, with high rates around Hellas basin and west of Tharsis but low rates around Margaritifer Sinus (where the observed valley network drainage density is nonetheless high). In the cold and icy scenario, snow migration is a function of both obliquity and surface pressure, and limited episodic melting is possible through combinations of seasonal, volcanic, and impact forcing. At surface pressures above those required to avoid atmospheric collapse (∼0.5 bar) and moderate to high obliquity, snow is transported to the equatorial highland regions where the concentration of valley networks is highest. Snow accumulation in the Aeolis quadrangle is high, indicating an ice‐free northern ocean is not required to supply water to Gale crater. At lower surface pressures and obliquities, both H2O and CO2 are trapped as ice at the poles and the equatorial regions become extremely dry. The valley network distribution is positively correlated with snow accumulation produced by the cold and icy simulation at 41.8∘ obliquity but uncorrelated with precipitation produced by the warm and wet simulation. Because our simulations make specific predictions for precipitation patterns under different climate scenarios, they motivate future targeted geological studies.